1993
DOI: 10.1182/blood.v82.9.2730.2730
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antitrophoblast antibodies in the sera of patients with anticardiolipin antibodies and fetal loss

Abstract: Women with anticardiolipin antibodies (ACLA) are at increased risk for fetal loss. One potential explanation for this outcome is that sera from these individuals contain antibodies reactive with trophoblast cells, which are involved in the establishment of the uteroplacental vasculature and maintenance of placental blood fluidity. To examine this hypothesis, we compared the incidence of trophoblast-reactive antibodies in 27 patients with ACLA and a history of fetal loss with that in 29 normal pregnant women. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…Although derived from measurement of cell proliferation in choriocarcinoma cell-lines (Jar and BeWo) exposed to aPL, this study provides strong supportive evidence for the decidual vasculopathỳ theory' of APS pregnancies. Others 69 have suggested the presence of antitrophoblast antibodies in APS pregnancies. Another recent study demonstrated reduced prolactin and insulin-like growth factor binding protein-1 expression in an in vitro model of endometrial stromal cell decidualization, suggesting that aPLs interfere with endometrial differentiation and that this may contribute to the incomplete formation of a functional feto-maternal interface.…”
Section: Evidence For Decidual Vasculopathy In Aps Pregnanciesmentioning
confidence: 98%
“…Although derived from measurement of cell proliferation in choriocarcinoma cell-lines (Jar and BeWo) exposed to aPL, this study provides strong supportive evidence for the decidual vasculopathỳ theory' of APS pregnancies. Others 69 have suggested the presence of antitrophoblast antibodies in APS pregnancies. Another recent study demonstrated reduced prolactin and insulin-like growth factor binding protein-1 expression in an in vitro model of endometrial stromal cell decidualization, suggesting that aPLs interfere with endometrial differentiation and that this may contribute to the incomplete formation of a functional feto-maternal interface.…”
Section: Evidence For Decidual Vasculopathy In Aps Pregnanciesmentioning
confidence: 98%
“…Other investigators have demonstrated the presence of antitrophoblast antibodies in APS patients with fetal loss. 13 They may impair the fusion of cytotrophoblastic cells in vitro to form syncytial cells, which is a critical step in the development and maturation of the villous trophoblast. 14 Following these and our previous studies demonstrating yolk sac damage caused in cultured rat embryos by serum from women with SLE/APS and RPL, we hypothesized that sera from these same patients would adversely affect the development of the placenta in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Os achados histopatológicos típicos em placentas de mães com SAF são trombose placentária e infarto. Entretanto, em muitos casos de perda gestacional, especialmente em abortamento espontâneo, não há evidências de trombose placentária, podendo haver outros mecanismos envolvidos na perda gestacional da SAF, como: alterações na secreção placentária de gonadotrofina coriônica humana (21) , reatividade cruzada dos anticorpos antifosfolípides com fosfolípides trofoblásticos e conseqüente exposição das vilosidades trofoblásticas à destruição por células maternas imunoefetoras (22) e redução dos níveis séricos de interleucina-3 induzida pelo anticorpo anticardiolipina (23) .…”
Section: Discussionunclassified